Exploring Helping Professionals Attitudes toward Clients with Antisocial Personality Disorder - Dunbar Jr, Edward T; Leierer, Stephen; Hurt-Avila, Kara; Elliott, Anna (International Journal of Psychosocial Rehabilitation, 2021)
There is a lack of research regarding helping professionals’ attitudes toward clients with antisocial personality disorder (ASPD). We examined factors associated with helping professionals’ attitudes toward clients with ASPD through an online survey using a modified version of a validated instrument. We found the following three factors: security, acceptance, and enjoyment influenced helping professionals’ attitudes towards clients with ASPD. Implications for clinical training, supervision, and education toward this population are discussed